ANALISA KURVA PERCENTAGE DEPTH DOSE (PDD) DAN PROFILE DOSE UNTUK LAPANGAN RADIASI SIMETRI DAN ASIMETRI PADA LINEAR ACCELERATOR (LINAC) 6 DAN 10 MV - Mariatul Khiftiyah; Eko Hidayanto; Zaenal Arifin (Youngster Physics Journal, 2014)
External radiotheraphy uses either symmetry or asymmetry radiation field. Percentage Depth Dose (PPD) and Dose Profile on either symmetry or asymmetry radiation field is an important parameter in conducting external therapy that is to analyze the result of parameters used for measurement, whether it is adjusted according to the specified tolerance limit. If the field size 10 X 10 cm2 is still in specified tolerance limit or it has been exceeding the limit.The techique used to collect the data was comparing whether dose distribution taken on the surface of either symmetry or asymmetry radiation field with maximum depth gained from Percentage Depth Dose (PPD) measurement and in the depth of 2 cm. By using device Linear Accelerator (LINAC) energy foton 6 and 10 MV in the radiation field with condition field no off-set and off-set 1 cm, off-set 3 cm and off-set 5 cm with Source Surface Distance (SSD) value 100 cm and in radiation field 10 X 10 cm2.The measurement result showed a change depth on Percentage Depth Dose (PPD) value in the off-set of radiation field 5 cm, on both kinds of energy caused by beam hardening, with value of symmetry and flatness 1.43% and 9.28%, for energy 6 MV and 2.2%, 6.59% for energy 10 MV. There was a change in file profile that caused declining value of flatness, and symmetry. Dose distribution because of this asymmetry radiation field should be concerned in clinical for application of asymmetry radiation field usage. Keywords: Percentage Depth Dose (PDD), Profile Dose, Symmetry, Asymmetry, flatness.